Kajian Penataan Jalur Pedestrian sebagai Unsur Fisik Pembentuk Karakter Visual dan Aktivitas Penggunjung: Studi Kasus : Gerbang Selamat Datang Simpang Kepur Kota Muara Enim - Mita Hargianti; Rika Septiana; Asia Afriani; Husnul Hidayat (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Pedestrian is one of the most important public spaces for urban areas. On the border of Muara Enim city has a pedestrian that attracts attention, namely the pedestrian welcome intersection kepur. Simpang Kepur pedestrian has a border gate that is the center of attention and the first impression when entering the city of Muara Enim so that it has the opportunity as a face or symbol of the identity of the city of Muara Enim. Visually, the existence of pedestrians and gates at the Kepur intersection looks quite attractive but functionally it is not in accordance with the characteristics of pedestrian activities on the pedestrian so that research is needed to rearrange the previous design so that the function of the pedestrian becomes even better. The method used is qualitative through observation based on facts and activities in the field. Analysis based on the impression of place and activity on the pedestrian. The results obtained that there is a need to change the appearance of the color processing so that the pedestrian becomes more alive, need to keep the pedestrian so that there is no loss or damage, the need for guardrails or vegetation / view barrier plants in the area behind or beside the pedestrian, rearrangement of plants that can absorb dust and can absorb noise, and arrangement of street furniture, namely visual recommendations for a wider bus stop design, replace permanent seating, replace permanent trash.